Ageing and Digital Technology Designing and Evaluating Emerging Technologies for Older Adults - Neves, Barbara Barbosa; Vetere, Frank (Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together Sociologists, Computer Scientists, Applied Scientists and Engineers to explore the design, implementation and evaluation of emerging technologies for older people. It offers an innovative and comprehensive overview, not only of the rapidly developing suite of current digital technologies and platforms, but also of perennial theoretical, methodological and ethical issues. As such, it offers support for researchers and professionals who are seeking to understand and/or promote technology use among older adults. The contributions presented here offer theoretical and methodological frameworks for understanding age-based digital inequalities, participation, digital design and socio-gerontechnology. They include ethical and practical reflections on the design and evaluation of emerging technologies for older people, as well as guidelines for ethical, participatory, professional and cross-disciplinary research and practice. In addition, they feature state-of-the-art, international empirical research on communication technologies, games, assistive technology and social media. As the first truly multidisciplinary book on technology use among ageing demographics, and intended for students, researchers, applied researchers, practitioners and professionals in a variety of fields, it will provide these readers with insights, guidelines and paradigms for practice that transcend specific technologies, and lay the groundwork for future research and new directions in innovation.